PENGARUH PERSEPSI PELAYANAN APARAT PAJAK, PERSEPSI PENGETAHUAN WAJIB PAJAK, DAN PERSEPSI PENGETAHUAN KORUPSI TERHADAP KEPATUHAN (Kajian Empiris Pada Wajib Pajak Orang Pribadi Yang Memiliki Usaha Di Kota Probolinggo Kecamatan Mayangan) - Susanto, Jessica Novia (University of Surabaya, 2013)
This study aims to analyze the antecedents of perception (quality of service tax authorities, learning, and corruption) of taxpayers against the imposition of income tax and their consequences to meet tax obligations in the meeting. Research conducted by questionnaire survey of personal taxpayers who have business in Probolinggo town. This research is an empirical study by purposive sampling technique in data collection. The data obtained through questionnaires by 99 and 99 respondents (100%) have given an answer. Data analysis was performed using regression analysis with SPSS for Windows 18.00. The results of this study indicate that (1) Quality of service tax authorities does not have significant effect on taxpayer perceptions about the taxation of income (2) learning does not have significant effect on the perception of taxpayers against the imposition of income tax, and (3)Corruption does not have significant effect on taxpayer perceptions about the taxation of income.